Characterization of serine/threonine protein phosphatases in RINm5F insulinoma cells. Issue 6 (December 1993) - Sjöhom, Åke; Honkanen, Richard E.; Berggren, Per-Olof
Abstract : This study investigates the occurrence and regulation of serine/threonine protein phosphatases (PPases) in insulin-secreting RINm5F insulinoma cells. PPases types 1 and 2A were identified in crude RINm5F cell homogenates by both enzymatic assay and Western blot analysis. We then characterized and compared the inhibitory actions of several compounds isolated from cyanobacteria, marine dinoflagellates and marine sponges, (viz. okadaic acid, microcystin-LR, calyculin-A and nodularin) cation-independent PPase activities in RINm5F cell homogenates. It was found that okadaic acid was the least potent inhibitor (IC50 ≈ 10 −9 M, IC100 ≈ 10 −6 M), while the other compounds exhibited IC50 values of ≈ 5·10 −10 M and IC100 ≈ 5·10 −9 M. The findings indicate that the inhibitory substances employed in this study may be used pharmacologically to investigate the role of serine/threonine PPases in RINm5F cell insulin secretion, a process that is likely to be regulated to a major extent by protein phosphorylation.